2009
DOI: 10.1271/bbb.80575
|View full text |Cite
|
Sign up to set email alerts
|

TheSchizosaccharomyces pombeSyntaxin 1 Homolog, Psy1, Is Essential in the Development of the Forespore Membrane

Abstract: Syntaxin is a component of t-soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE), which is responsible for docking membrane vesicles at the target membrane and is highly conserved among eukaryotes. In the fission yeast Schizosaccharomyces pombe, the psy1(+) gene encoding a syntaxin 1 homolog was originally isolated as a multicopy suppressor of the sporulation-deficient mutant, spo3, but little is known about the way Psy1 is involved in sporulation. Here we report the isolation of a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 1 publication
3
31
0
3
Order By: Relevance
“…The present study, together with our previous work (6,7,40), shows that all of the fission yeast PM SNARE components play a critical role in sporulation. Unlike S. cerevisiae, S. pombe has a sole gene encoding each of the PM SNARE components.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The present study, together with our previous work (6,7,40), shows that all of the fission yeast PM SNARE components play a critical role in sporulation. Unlike S. cerevisiae, S. pombe has a sole gene encoding each of the PM SNARE components.…”
Section: Discussionsupporting
confidence: 79%
“…As a result, it has been suggested that spore wall materials are transported by secretory vesicles. Because the sporulation-deficient sec9-10 and psy1-S1 mutant cells form no spores, possibly due to severe defects in FSM formation, we could not examine whether the PM SNAREs are indeed required for spore wall formation (7,40). Compared with sec9-10 and psy1-S1, syb1-S1 exhibited a milder phenotype, and most of the syb1-S1 spores germinated.…”
Section: Discussionmentioning
confidence: 99%
“…Psy1 is a plasma membrane-resident t-SNARE protein that is homologous to budding yeast Sso1 and Sso2 (1) and human syntaxin-1 (2). The gfp-psy1 fusion gene was integrated at the ade6 locus on chromosome III (14).…”
Section: Methodsmentioning
confidence: 99%
“…A candidate could be the forespore membrane, which is a precursor of the spore plasma membrane that surrounds nuclei during MII 24 . The forespore membrane was visualized with the GFPtagged tSNARE protein Psy1/Syntaxin 1 (GFPPsy1) 25 . As reported previously 26 , the forespore membrane started to assemble around the SPBs in a crescent shape after they were separated by ipMTs (15 min; Fig.…”
Section: Normal Chromosome Segregation In Absence Of Ipmts In MIImentioning
confidence: 99%